Kebijakan Publik Yang Partisipatif Dan Komunikatif - Yuli Tirtariandi El Anshori; Enceng '; Ayi Karyana (Universitas Riau, 2012)
This article summarizes theresults of a study to analyze how the process of defining urban planning policy issued by the CityGovernment Pangkalpinang particularly in the field of transportation. This policy is about one-way regulation which was enacted in 2011 on certain roads. The study was conducted to find outwhat are the barriers to the implementation of participatory and communicative urban planningpolicies. The research method uses a qualitative approach, descriptive analysis and use casestudy design. Datas were collected through interviews, observation, and documentary studies.The results showed that the policy of one-way streets that carried by the local government wasless participatory. Not all stakeholders are involved in the formulation of policy. The City Governmentdid not respond to City Council to delay implementation of the policy because it found manyproblems in the test phase. Communication is woven by the City Government is also less effectiveso that the policy was not optimally socialized.